Prognostic value of staging laparotomy in supradiaphragmatic clinical stage I and II Hodgkin's disease - Vovk, Marjeta (Radiology and oncology (Ljubljana), 1996)
In the period 1974-1989, 219 patients with supradiaphragmatic clinical stage I and II Hodgkin's disease were treated at the Institute of Oncology in Ljubljana; of these 95 (43%) patients underwent staging laparotomy. Of laparotomized patients, those with pathological stage III-IV, and of non-laparotomized, those with unfavorable prognostic factors (B-symptoms, bulky mediastinum) received chemotherapy: the remaining patients were treated by irradiation. No statistically significant difference in the survival and disease-free survival between laparotomized and nonlaparotomized patients could be found.
Keywords: diagnostika; Hodgkinova bolezen; laparotomija; onkologija